Correlation of diagnostic tests ANB Angle, Wits assessment and A:B ratio in determination of intermaxillary sagital relationship - Emily Patricia Icaza Terán; María Angélica Terreros de Huc (Universidad de Guayaquil, 2023)
INTRODUCTION: Among the diagnostic tests to evaluate sagittal maxillomandibular skeletal discrepancies and the different changes that occur during growth, the following are presented: ANB angle, (Riedel 1948); the Wits Assessment, (Jacobson 1975) of linear type and the A:B Ratio (Terreros 2020), study of geometric proportions, as alternative diagnostic tests to establish the intermaxillary sagittal relationship. OBJECTIVE: To analyze the correlation of intermaxillary sagittal appreciation between angular diagnostic tests (ANB), linear (WITS) and A:B ratio (geometric proportional) in different facial types. MATERIALS AND METHODS: Comparative radiographic study with a quantitative, cross-sectional, retrospective approach in search of 55 cephalometric radiographs of boys and girls aged 8 to 13 years, descriptive-analytical design study, deductive method. RESULTS: In this study it was shown that between the ANB Angle and the A:B Ratio there is a moderate negative relationship of -0.59, between the Wits assessment and the A:B Ratio the correlation is -0.504, which indicates that there is a moderate negative relationship and Angle ANB with the Wits Rating the value is 0.501 which indicates that there is a moderate positive correlation. CONCLUSION: It is established that the ANB angle diagnostic test uses the Nasion point as a reference and that its position affects its diagnosis. There is a moderate to good correlation between the diagnostic tests ANB Angle, A:B Ratio and Wits Assessment in the determination of the intermaxillary sagittal relationship.